Kebijakan Perubahan Kurikulum 2013 Ke Kurikulum Merdeka Pada Pembelajaran Mata Pelajaran PPKn Di SMPN 1 Plumpang - Arju Wijiono; Darinda Trisna Wiharnik; Gretha Arya Mahardika (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
The curriculum provides an overview of the country's educational goals. According to this view, the curriculum becomes the foundation or outlook on life. How is the learning of PPKn subjects after the 2013 curriculum change policy to an independent curriculum at SMPN 1 Plumpang. This research method uses descriptive qualitative research methods. Qualitative research methods are the right type of research method to reveal a person's perceptions only through direct contact. The research was conducted at SMP Negeri 1 Plumpang. The researcher's data collection technique was to conduct interviews with PPKn teachers then collect, conclude and describe changes from K13 to the Independent Curriculum. This curriculum change has had both positive and negative impacts. In the 2013 curriculum, Civics subjects have been improved from before. in the independent curriculum, the PPKn subject is helped by the existence of the Pancasila Student Profile which aims to create student identity in Indonesia. The implementation of the 2013 curriculum and the independent curriculum in the PPKn subject is not much different. This is because the content presented to students is the same. Apart from that, implementing it in the 2013 curriculum is more difficult because of the lack of training for teachers, whereas in the independent curriculum it is easier because it is more flexible and is helped by the existence of the Pancasila Student Profile.